2019
DOI: 10.1016/j.heliyon.2019.e01983
|View full text |Cite
|
Sign up to set email alerts
|

Competence, autonomy, and relatedness in the classroom: understanding students’ motivational processes using the self-determination theory

Abstract: The purpose of the current study is to examine the relationships between need satisfaction, motivation, and outcomes as well as the differential effects of the three psychological needs. The sample consisted of 1549 students from 10 secondary schools in Singapore. Structural equation modelling (SEM) analysis showed that students’ psychological needs are positively related to autonomous motivation, and this in turn, lead to higher enjoyment, value and lower pressure. On the other hand, the three psychological n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 28 publications
(30 reference statements)
7
70
1
3
Order By: Relevance
“…In addition to formal theory development, SDT has been applied to many domains, including health and medicine [38,39], learning [40,41], and virtual environments [36,37,42]. A study in [39] applied self-determination theory to test the influence of autonomous and controlled motivations on the prediction of health-related behaviors.…”
Section: Self-determination Theorymentioning
confidence: 99%
“…In addition to formal theory development, SDT has been applied to many domains, including health and medicine [38,39], learning [40,41], and virtual environments [36,37,42]. A study in [39] applied self-determination theory to test the influence of autonomous and controlled motivations on the prediction of health-related behaviors.…”
Section: Self-determination Theorymentioning
confidence: 99%
“…Students' motivation in getting higher academic motivation corresponds with Wang et al (2019) opinion that when students are highly motivated, they tend to stay engaged and persist longer. Moreover, students will acquire knowledge in more coherent forms, apply their knowledge more often, and achieve higher academic performance over the long term.…”
Section: Participant Responses To the Implementation Of Onmipamentioning
confidence: 92%
“…Moreover, students will acquire knowledge in more coherent forms, apply their knowledge more often, and achieve higher academic performance over the long term. Wang et al (2019) also state that for decades, researchers have established the connection between students' motivation and many positive learning effects.…”
Section: Participant Responses To the Implementation Of Onmipamentioning
confidence: 99%
“…In turn, when teachers' needs were fulfilled, they were self-determined and hence they engaged in motivational strategies such as gain understanding of students, provide instrumental help and support and provide a meaningful rationale for students. In addition, studies have shown that the type of motivational strategy used by teachers does have significant consequences on students (Wang et al, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%